2017
DOI: 10.1111/1475-679x.12174
|View full text |Cite
|
Sign up to set email alerts
|

Does Corporate Social Responsibility (CSR) Create Shareholder Value? Evidence from the Indian Companies Act 2013

Abstract: In 2013, a new law required Indian firms, which satisfy certain profitability, net worth, and size thresholds, to spend at least 2% of their net income on corporate social responsibility (CSR). We exploit this regulatory change to isolate the shareholder value implications of CSR activities. Using an event study approach coupled with a regression discontinuity design, we find that the law, on average, caused a 4.1% drop in the stock price of firms forced to spend money on CSR. However, firms that spend more on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
254
7
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(279 citation statements)
references
References 74 publications
13
254
7
5
Order By: Relevance
“…This is the responsibility of board of directors to ensure spending of 2% of average net profit on approved CSR activities and to disclose CSR policy and initiatives on company's website and in board's report (Manchiraju & Rajgopal, ). Companies can include several CSR activities in their policy, which range from eradication of hunger and poverty to community problem resolution projects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is the responsibility of board of directors to ensure spending of 2% of average net profit on approved CSR activities and to disclose CSR policy and initiatives on company's website and in board's report (Manchiraju & Rajgopal, ). Companies can include several CSR activities in their policy, which range from eradication of hunger and poverty to community problem resolution projects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, based on international evidence, [24] found a consistent positive relationship holds only in the long run and, therefore, short-term stock returns are not related to CSR except for European firms. The authors of [25] found that the firms forced to spend money on CSR activities experience a 4.1% drop in their stock prices. The work [12] found no relationship between CSR and risk-adjusted stock return.…”
Section: Csr and Value Relevance Of Financial Reportingmentioning
confidence: 99%
“…Corporate social responsibility (CSR) reporting represents a form of voluntary corporate non-financial disclosure for managers to signal their trustworthiness and communicate private information to investors. The literature indicates that CSR information has incremental value to investors when evaluating, for example, companies' future financial performance (Orlitzky et al, 2003;Servaes and Tamayo, 2013;Manchiraju and Rajgopal, 2017;Clarkson et al, 2019), cost of equity capital (Dhaliwal et al, 2011), labour productivity (Christensen et al, 2017), earning quality (Kim et al, 2012), and even the propensity to commit high-profile corporate misconduct (Christensen, 2016). Given such evidence, companies both within the United States and globally are increasingly providing standalone CSR reports voluntarily, in addition to traditional corporate financial disclosures, in response to the growing demand for CSR information by stakeholders (KPMG, 2015).…”
mentioning
confidence: 99%